Calcitriol‐Dependent and ‐Independent Regulation of Intestinal Calcium Absorption, Osteoblast Function, and Skeletal Mineralization during Lactation and Recovery in Mice. (11th October 2022) - Ryan, Brittany A.; McGregor, Narelle E.; Kirby, Beth J.; Al‐Tilissi, Abdelkhayoum; Poulton, Ingrid J.; Sims, Natalie A.; Kovacs, Christopher S.
ABSTRACT: Recovery from lactation‐induced bone loss appears to be calcitriol‐independent, since mice lacking 1‐alpha‐hydroxylase or vitamin D receptor (VDR) exhibit full skeletal recovery. However, in those studies mice consumed a calcium‐, phosphorus‐, and lactose‐enriched "rescue" diet. Here we assessed whether postweaning skeletal recovery of Vdr null mice required that rescue diet. Wild type (WT) and Vdr null mice were raised on the rescue diet and switched to a normal (1% calcium) diet at Day 21 of lactation until 28 days after weaning. Unmated mice received the same regimen. In WT mice, cortical thickness was significantly reduced by 25% at 21 days of lactation and was completely restored by 28 days after weaning. Three‐point bending tests similarly showed a significant reduction during lactation and full recovery of ultimate load and energy absorbed. Although Vdr null mice exhibited a similar lactational reduction in cortical thickness and mechanical strength, neither was even partially restored after weaning. Unmated mice showed no significant changes. In micro‐computed tomography scans, diaphyses of Vdr null femora at 28 days after weaning were highly porous and exhibited abundant low‐density bone extending into the marrow space from the endocortical surface. To quantify, we segregated bone into low‐, mid‐, and high‐density components. In WT diaphyses, high‐density bone was lost during lactation and restored after weaning. Vdr null mice also lost high‐density bone during lactation but did not replace it; instead, they demonstrated a threefold increase in low‐density bone mass. Histology revealed that intracortical and endocortical surfaces of Vdr null bones after weaning contained very thick (up to 20 micron) osteoid seams, covered with multiple layers of osteoblasts and precursors. We conclude that during the postweaning period, osteoblasts are potently stimulated to produce osteoid despite lacking VDRs, and that either calcitriol or a calcium‐enriched diet are needed for this immature bone to become mineralized. © 2022 American Society for Bone and Mineral Research (ASBMR).